Following the World Health Organization's Recommendation of Exclusive Breastfeeding to 6 Months of Age Does Not Impact the Growth of Rural Gambian Infants. Issue 2 (21st December 2016) - Eriksen, Kamilla G; Johnson, William; Sonko, Bakary; Prentice, Andrew M; Darboe, Momodou K; Moore, Sophie E
Abstract: Background: The WHO recommends exclusive breastfeeding (EBF) for the first 6 mo of life. Objective: The objective of this study was to assess the benefit of EBF to age 6 mo on growth in a large sample of rural Gambian infants at high risk of undernutrition. Methods: Infants with growth monitoring from birth to 2 y of age ( n = 756) from the ENID (Early Nutrition and Immune Development) trial were categorized as exclusively breastfed if only breast milk and no other liquids or foods were given. EBF status was entered into confounder-adjusted multilevel models to test associations with growth trajectories by using >11, 000 weight-for-age (WAZ), length-for-age (LAZ), and weight-for-length (WLZ) z score observations. Results: Thirty-two percent of infants were exclusively breastfed to age 6 mo. The mean age of discontinuation of EBF was 5.2 mo, and growth faltering started at ∼3.5 mo of age. Some evidence for a difference in WAZ and WHZ was found between infants who were exclusively breastfed to age 6 mo (EBF-6) and those who were not (nEBF-6), at 6 and 12 mo of age, with EBF-6 children having a higher mean z score. The differences in z scores between the 2 groups were small in magnitude (at 6 mo of age: 0.147 WAZ; 95% CI: −0.001, 0.293 WAZ; 0.189 WHZ; 95% CI: 0.038, 0.341 WHZ). No evidence for a difference between EBF-6 and nEBF-6 infants was observed for LAZ at any time point (6, 12, and 24 mo of age). Furthermore, a higher mean WLZ at 3 mo of age was associated with a subsequent higher mean age at discontinuation of EBF, which implied reverse causality in this setting (coefficient: 0.060; 95% CI: 0.008, 0.120). Conclusion: This study suggests that EBF to age 6 mo has limited benefit to the growth of rural Gambian infants. This trial was registered at http://www.isrctn.com as ISRCTN49285450.